2017
DOI: 10.1002/ana.24928
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring epilepsy surgery with fast ripples in the intraoperative electrocorticogram

Abstract: FRs that persist before and after resection predict poor postsurgical outcome. These findings hold for different tailoring approaches. FRs can thus be used for tailoring epilepsy surgery with repeated intraoperative ECoG measurements. Ann Neurol 2017;81:664-676.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 50 publications
3
141
0
1
Order By: Relevance
“…It remains unknown how the utility of MI is altered by different electrode types (eg, disk vs depth electrodes), different montage (eg, common average reference vs bipolar montage), anesthesia conditions, and intracranial electrode placement approaches (eg, large vs limited coverage). A retrospective study of 54 patients reported that the occurrence of HFA >250 Hz on intraoperative ECoG immediately following cortical resection was associated with a greater risk of seizure recurrence . One logical next step would be to determine whether quantitative measurement of MI during intraoperative ECoG recording will provide useful information to localize the EZ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It remains unknown how the utility of MI is altered by different electrode types (eg, disk vs depth electrodes), different montage (eg, common average reference vs bipolar montage), anesthesia conditions, and intracranial electrode placement approaches (eg, large vs limited coverage). A retrospective study of 54 patients reported that the occurrence of HFA >250 Hz on intraoperative ECoG immediately following cortical resection was associated with a greater risk of seizure recurrence . One logical next step would be to determine whether quantitative measurement of MI during intraoperative ECoG recording will provide useful information to localize the EZ.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 54 patients reported that the occurrence of HFA >250 Hz on intraoperative ECoG immediately following cortical resection was associated with a greater risk of seizure recurrence. 15 One logical next step would be to determine whether quantitative measurement of MI during intraoperative ECoG recording will provide useful information to localize the EZ.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…46,47 This suggests that it is critical to disconnect networks generating HFOs rather than remove all areas that generate HFOs prior to surgery. 47 It might also explain the negative association with postoperative seizure outcome in some patients, in whom HFO rates were assessed in presurgical chronic intracranial EEG recordings. An example of a patient who had residual fast ripples in the postsurgical electrocorticogram and who was not seizure-free after surgery is given in Figure 1.…”
Section: Hfos As Markers Of the Epileptogenic Zonementioning
confidence: 99%